Human Rights of Children: With special reference to Risod Block, Washim District - Dr. Pramodkumar Nandeshwar (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2019)
Rights are those conditions of human life, without which generally a person cannot attain his highest form. Today the entire human race is suffering from exploitation, atrocities, corruption, etc. The child is the biggest victim of human rights violations. It is not only a problem for the human race but also a big danger. Poverty, illiteracy, lack of life, and social system come as the factors that deprive children of human rights. In relation to the rights of children, it was announced in 1924 at the Geneva Convention, according to which provisions were made regarding the protection and care of the life of children. According to the amendment, child labor is done in more evidence on the resort development block. Child labor is widely seen in rural areas due to people's lack of knowledge regarding the child labor law and the anti-child labor clause in the Indian Constitution. This inhuman act has been cursed by the law. This practice has been banned through legislation.